Yours For A Song - Dana Suesse::::::::: (Robbins Music Corporation)
Piano and vocal score, 5 p. On cover: Featured in Billy Roses Aquacade 1940 Golden Gate International Exposition, staged by John Murray Anderson Photo of Tower of the Sun on front cover Publishers advertisements on p.[2] and verso of last leaf.